Fostering technological dynamism : evolution of thought on technological development processes and competitiveness : a review of the literature (UN New YorkUS, 1996)
Focuses on how countries - in particular developing countries - acquire and gain mastery over new technology, including the organization of production processes; and, on how technology transfer and the accumulation of technological capacity affect competitiveness at the enterprise and national levels.
Bibliography: p. [139]-174